Modeling and simulation of air pollutant distribution in street canyon area with Skytrain stations - Suranath Chomcheon; Nathnarong Khajohnsaksumeth; Benchawan Wiwatanapataphee; Xiangyu Ge (Advances in Difference Equations, 2019)
Abstract This paper focuses on effects of the wind flow velocity on the air flow and the air pollution dispersion in a street canyon with Skytrain. The governing equations of air pollutants and air flow in this study area are the convection–diffusion equations of species concentration and the Reynolds-averaged Navier–Stokes (RANS) equations of compressible turbulent flow, respectively. Finite element method is utilized for the solution of the problem. To investigate the impact of the air flow on the pattern of air pollution dispersion, three speeds of inlet wind in three different blowing directions are chosen. The results illustrate that our model can depict the airflows and dispersion patterns for different wind conditions.